Experimental evaluation of fatty acid composition influence on Jatropha biodiesel physicochemical properties - Reddy, A.N.R.; Saleh, A.A.; Islam, Md Saiful; Hamdan, Sinin; Rahman, Md Rezaur; Masjuki, Haji Hassan (AIP Publishing, 2018)
The physiochemical properties of biodiesel are significantly influenced by its fatty acid composition (FAC). This research investigates FAC of Jatropha biodiesel (JB) synthesized using feedstocks originated from the east (JBEM) and west (JBWM) Malaysian regions together with biofuel properties. The critical properties of pure biodiesels and blends were analysed according to ASTM D6751/EN 14214 standards. The JB properties were precisely regulated by its FAC features such as saturated fatty acids (SFAs), unsaturated fatty acids (USFAs), degree of unsaturation, and long chain saturated factor. The influence of SFA and USFA was inversely associated over biodiesel properties. The presence of higher SFA greatly affects biodiesel properties like the cetane number, cold filter plugging point, kinematic viscosity, density, cloud point, and pour point; conversely, the fuel properties such as oxidation stability, iodine value, acid value, water content, and flash point were improving with USFA contents. Blending of biofuels with petro diesels considerably improved their fuel properties.